2020
DOI: 10.1093/abbs/gmz158
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ establishes interferon-stimulated gene-mediated antiviral state against Newcastle disease virus in chicken fibroblasts

Abstract: Newcastle disease virus (NDV) causes severe economic losses through severe morbidity and mortality and poses a significant threat to the global poultry industry. Significant efforts have been made to develop novel vaccines and therapeutics; however, the interaction of NDV with the host is not yet fully understood. Interferons (IFNs), an integral component of innate immune signaling, act as the first line of defense against invading viruses. Compared with the mammalian repertoire of IFNs, limited information is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…On the contrary, in IFN-α, there was a downregulation. Previous studies have shown that large amounts of IFN are produced by various host cells when infected with NDV [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in IFN-α, there was a downregulation. Previous studies have shown that large amounts of IFN are produced by various host cells when infected with NDV [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both IFN-α and IFN-β belong to type І interferons, and they are crucial to the regulation of innate immune responses ( Ivashkiv and Donlin, 2014 ). IFN-γ is a vital mediator for the immunity of chickens with antimicrobial properties, and it also acts as a biomarker for the activation of the innate immune system ( Liu et al., 2009 ; Yang et al., 2020 ). In the early response to microbial infection, interferons may upregulate the transcription of antiviral genes to interrupt the viral replication, providing sufficient time for the immune response to develop ( Samuel, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 also induced IFN-γ production in this study and enhanced the CMI response as reported earlier [ 37 ]. Further, IFN-γ induced Th-1 response along with adjuvant activity as evidenced by Xin Yang et al, 2020 [ 38 ]. IL-4 expression induced increased antibody production in the vaccinated groups.…”
Section: Discussionmentioning
confidence: 99%